2016
DOI: 10.1371/journal.pone.0158705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPPU on Carbohydrate and Endogenous Hormone Levels in Young Macadamia Fruit

Abstract: N-(2-Chloro-4-pyridyl)-N′-phenylurea (CPPU) is a highly active cytokinin-like plant growth regulator that promotes chlorophyll biosynthesis, cell division, and cell expansion. It also increases fruit set and accelerates fruit enlargement. However, there has been no report about the effect of CPPU on fruit development and its physiological mechanism in macadamia. In this study, we investigated the effect of CPPU treatment at early fruit development via foliar spray or raceme soaking at 20 mg·L-1 on fruit set an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…It encourages the formation of shoots on growing vegetative growths on transplant and increasing the number of leaves by increasing the opening of lateral buds and the development of chloroplasts and chlorophyll biosynthesis through a course on the physiological processes responsible for those The increase in Photosynthesis, breathing and nutrient transfer from root to leaf increases the area of vegetative growths and delays their aging. This explains the increase in vegetative growth (Gundea , 2003, Zeng , 2016and Zhang , 2013 and These results are in agreement with those obtained by (Bhat , 2011 and Al-Karam , 2016) .…”
Section: Resultssupporting
confidence: 89%
“…It encourages the formation of shoots on growing vegetative growths on transplant and increasing the number of leaves by increasing the opening of lateral buds and the development of chloroplasts and chlorophyll biosynthesis through a course on the physiological processes responsible for those The increase in Photosynthesis, breathing and nutrient transfer from root to leaf increases the area of vegetative growths and delays their aging. This explains the increase in vegetative growth (Gundea , 2003, Zeng , 2016and Zhang , 2013 and These results are in agreement with those obtained by (Bhat , 2011 and Al-Karam , 2016) .…”
Section: Resultssupporting
confidence: 89%
“…In addition, fruit growth is tightly related to the availability of carbohydrate, because fruit is a very strong metabolic sink. Many studies confirmed that CKs was demonstrated to regulate carbohydrate allocation in fruit [ 65 , 66 ]. We thought that maybe another reason why CPPU induced parthenocarpic fruit was consistently bigger than the fruit induced by other PRGs.…”
Section: Resultsmentioning
confidence: 93%
“…Macadamia (Macadamia ternifolia F. Muell), a genus of the proteaceae family, is now being widely cultivated in Australia, United States, and China (Navarro and Rodrigues, 2016;O'Connor et al, 2015;Wallace and Walton, 2011;Yang et al, 2015;Zeng et al, 2016). Macadamia nut oil (MNO) contains vitamin E, sterols, and phenolic acids (Maguire et al, 2004;Proschogo et al, 2012;Quinn and Tang, 1996).…”
Section: Introductionmentioning
confidence: 99%